Sale of Price Information by Exchanges: Does It Promote Price Discovery? - Cespa, Giovanni; Foucault, Thierry (Management Science, 2014)
Exchanges sell both trading services and price information. We study how the joint pricing of these products affects price discovery and the distribution of gains from trade in an asset market. A wider dissemination of price information reduces pricing errors and the transfer from liquidity traders to speculators. This effect reduces the fee that speculators are willing to pay for trading. Therefore, to raise its revenue from trading, a for-profit exchange optimally charges a high fee for price information so that only a fraction of speculators buy this information. As a result, price discovery is not as efficient as it would be with free price information. This problem is less severe if the exchange must compensate liquidity traders for a fraction of their losses. This paper was accepted by Wei Xiong, finance.